(untitled) - Inoue, Junnosuke (London, 1931)
This book introduce the war period, 1914 - 1918, the difficulties of the exchange position. Attempts to solve the exchange. The period from the armistice to the earthquake of 1923...
Keywords: Ngân hàng và hoạt động ngân hàng,Banks and banking; Nhật Bản,Japan